The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/jjco/hyt176
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quality of Life Based on Surgical Technique in Patients with Breast Cancer

Abstract: Objective: More than 80% of women with breast cancer survive for more than 5 years; quality of life is an important issue in these patients. The aim of this study was to assess differences in quality of life among patients who have undergone breast-conserving surgery, total mastectomy and immediate reconstruction after total mastectomy. Methods: A cross-sectional study was conducted during follow-up visits. Women who underwent surgical treatment at least 2 years prior were eligible if they were aged 20 -70 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 30 publications
7
58
1
6
Order By: Relevance
“…In a cross-sectional study by Holly et al (22), depressive symptoms were equal in the mastectomy with and without BR groups, whereas more depressive symptoms were found in the mastectomy without BR group in other studies (12,23). Likewise, contrasting reports have been published regarding quality of life (QoL), which was equal for patients with and without BR after mastectomy in several studies (13,24), whereas a better QoL and better psychological/emotional functioning was presented in the BR group in other reports (8,10,11).…”
Section: Discussionmentioning
confidence: 97%
“…In a cross-sectional study by Holly et al (22), depressive symptoms were equal in the mastectomy with and without BR groups, whereas more depressive symptoms were found in the mastectomy without BR group in other studies (12,23). Likewise, contrasting reports have been published regarding quality of life (QoL), which was equal for patients with and without BR after mastectomy in several studies (13,24), whereas a better QoL and better psychological/emotional functioning was presented in the BR group in other reports (8,10,11).…”
Section: Discussionmentioning
confidence: 97%
“…There were, however, a minority of patients who reported that their body image has been very much affected by their surgery. In order to fully understand why some patients have more body image concerns, it is necessary to consider BIS scores in the context of their age, time since surgery and the type of surgery they underwent as well as look- Many studies have shown that the type of surgical procedure undergone has had an effect on post-surgical body image [18,19]. A similar study carried out in the UK showed that a significantly better body image was observed in patients after breast conservation compared with mastectomy with or without reconstruction [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the above Japanese study, there was a higher Outcomes After Breast Surgery J Curr Surg. 2016;6(2):46-51 proportion of women in the mastectomy only group who had chemotherapy and axillary dissection, compared with MR and WLE [19]. These differences in disease prognosis may have influenced patient perspective on body image.…”
Section: Discussionmentioning
confidence: 99%
“…Изучение психоэмоционального состояния 39 боль-ных РМЖ, перенесших РМЭ, и 28 больных, которым была произведена отсроченная реконструкция молоч-ной железы, показало ослабление на протяжении 1-6 лет признаков дистресса у всех пациенток, однако общий индекс тяжести дистресса был выше у послед-ней группы [20]. Качество жизни, связанное со здоро-вьем, с учетом психоэмоциональной сферы, по дан-ным [21], было выше у больных РМЖ, перенесших органосохраняющие операции, по сравнению с пере-несшими РМЭ с реконструкцией и без, а по данным [22,23] -у пациенток, перенесших РМЭ с одномо-ментной реконструкцией молочной железы.…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified